1984
DOI: 10.1016/s0006-3495(84)84153-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-channel studies on linear gramicidins with altered amino acid sequences. A comparison of phenylalanine, tryptophane, and tyrosine substitutions at positions 1 and 11

Abstract: The relation between chemical structure and permeability characteristics of transmembrane channels has been investigated with the linear gramicidins (A, B, and C), where the amino acid at position 1 was chemically replaced by phenylalanine, tryptophane or tyrosine. The purity of most of the compounds was estimated to be greater than 99.99%. The modifications resulted in a wide range of conductance changes in NaCl solutions: sixfold from tryptophane gramicidin A to tyrosine gramicidin B. The conductance changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 55 publications
5
83
0
Order By: Relevance
“…The subunit/subunit interface formed by the first five residues of each subunit near the bilayer center is important for the single channel lifetime (57,61,62). The lifetime also depends on hydrophobic matching between the channel exterior and the host lipid bilayer (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subunit/subunit interface formed by the first five residues of each subunit near the bilayer center is important for the single channel lifetime (57,61,62). The lifetime also depends on hydrophobic matching between the channel exterior and the host lipid bilayer (25).…”
Section: Discussionmentioning
confidence: 99%
“…Implication for Membrane Proteins-Although Trp often is considered to be hydrophobic, Trp residues have long been described as "anchoring" residues in membrane proteins (2,4,5), and as early as 1984, it was found, using [Trp 1 ]gA channels, that there is a significant penalty associated with burying Trp residues in the bilayer core (62). More recently, it was shown that Trps near the C terminus of a membrane-spanning ␣-helix display a distinctly different behavior from those near the N terminus, reflected in large differences in the allowed side chain torsion angles and ring motions, highlighting the directionality of an ␣-helix relative to the bilayer/solution interface (67).…”
Section: Discussionmentioning
confidence: 99%
“…Substitutions at the first position of [Val',Gly2]gA, where the two monomers join to form the membrane-spanning dimer, can have large effects on the single-channel conductance and the average channel duration (Mazet et al, 1984;Russell et al, 1986;Durkin et al, 1990). Position-one substitutions alter channel function predominantly through electrostatic interactions between the passing ions and the dipole of the side chain .…”
mentioning
confidence: 99%
“…The Phe-1 gramicidin A analog was prepare by (v) diffusion away from the channel. A number of studies have been made to determine the equilibrium binding con-the semi-synthesis method (26)(27)(28). Sodium dodecyl sulfate-d25 (SDS), trifluoroethanol (TFE), and deuterium oxstants for the cation-channel complex and the transport rates (1,14,15).…”
Section: Methodsmentioning
confidence: 99%